Adaptasi Pendidikan Islam Anak Usia Dini di Era Digital pada RA GUPPI Kalak - Sanjaka Yekti (Lembaga Yasin AlSys, 2026)
Early childhood Islamic education plays a strategic role in shaping children’s character, moral, and spiritual development from an early age, while technological advancement in the digital era presents both opportunities and challenges for the internalization of Islamic values. This study aimed to analyze the success of early childhood Islamic education in the digital era through the adaptation of values and learning methods at RA GUPPI Kalak. The research employed a qualitative approach with a case study design, involving the principal, teachers, and parents of students as research subjects. Data were collected through observation, interviews, and documentation, and were analyzed interactively through the stages of data reduction, data display, and conclusion drawing. The findings showed that the adaptation of Islamic values encompassing aqidah, ibadah, and akhlak into guided and controlled digital media–based learning supported the success of early childhood Islamic education. The use of digital media increased children’s learning enthusiasm, facilitated their understanding of Islamic values, and contributed to the emergence of religious behaviors, the strengthening of moral understanding, and the ability to use technology in a positive manner. This study concludes that integrating Islamic values with appropriate digital learning methods keeps early childhood Islamic education relevant, adaptive, and effective in the digital era, and underscores the importance of adult guidance in directing technology use so that it aligns with the goals of Islamic education.